Ensuring 3es and Responsiveness in the Delivery of Educational Services in the Autonomous Region in Muslim Mindanao, Philippines - Sapia Moalam Abdulrachman; Badriya P. Makol (Jurnal Studi Pemerintahan, 2013)
The Autonomous Region in Muslim Mindanao (ARMM) is a public organization in the Philippines located in between the national government and the local governments. It performs unique functions quite distinct from other public organizations in the country, as it performs both political and administrative functions. Using unobtrusive research design, as it relies on mostly secondary data, this paper analyzes the educational system in the region and proposes strategies in attaining administrative efficiency, economy, effectiveness and responsiveness. The paper starts with the introduction which consist of the background and statement of the problem. It is followed by a review of theoretical perspective and then by the research methodology. The fourth part portrays the findings of the study which include: DepEd ARMM resources; the management of DepEd ARMM, and the management outputs such as: net enrollment ratio, achievement rate and litaracy rate. The fifth part of the paper deals with the analyses and conclusion. The paper concludes that in addition to certain structural innovation, inculcation of appropriate work ethics in accordance with the Ethical Standards Act, the Anti-Corruption Law, the Civil Service Rules and Regulations as well as the Islamic Practices on Employment must be enshrined in the reform agenda. Finally, among other things that could facilitate the attainment of 3Es and R in the deivery of educational services is a strategy that requires the joint collaboration and teamwork between the civil society, non-government organizations and government organizations in the region.